Bouncing back: a longitudinal examination of challenge within football academy environments - Papastaikoudis, Foivos; Collins, Rosie; Collins, Dave (Frontiers in Sports and Active Living, 2024)
Introduction Although substantial research indicates that challenge plays a big role in the development of talent, little is known of the experiences of young performers as they negotiate and learn from these challenges. Methods As such, to better understand the nature and impact of challenge on the Talent Development (TD) pathway, we longitudinally tracked nine young footballers from progressive age-bands (five aged 11 years and four aged 14) as they experienced challenge over a 15-month period using a mixed-methods design. Five semi-structured interviews separated by three months were conducted, and data were analysed via thematic analysis. Results Our findings suggested that participants encountered recurrent challenging events, categorised into common/uncommon, planned/unplanned, individual-focused/group-focused challenges. Support for the benefits of challenges was pervasive throughout the data with participants progressing through stages with each challenge (drop, rebound and growth). However, the magnitude and rate at which participants experienced these stages was highly idiosyncratic. Indeed, the perceived impact, scale, and, ultimately, consequential developmental impact of these challenges appeared to vary greatly with participants displaying different responses to similar events. Such differences were underpinned by several individual factors (such as prior experiences and perceived coping skills), contextual characteristics of the challenge (such as type and timing) and support around the challenge (such as priming and reflection opportunities). Conclusion Implications include the need for coaches and psychologists to systematically assess and carefully monitor the individual circumstances, needs and skillset of young performers and use this information as a platform for deploying individualised, timely and developmentally appropriate challenges along with relative support to ensure optimal learning and growth from them.